2016
DOI: 10.1186/s12891-016-0946-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of self-report questions to examine the prevalence of musculoskeletal problems: a test-retest study

Abstract: BackgroundCase definition has long been an issue for comparability of results obtained for musculoskeletal pain prevalence, however the test-retest reliability of questions used to determine joint pain prevalence has not been examined. The objective of this study was to determine question reliability and the impact of question wording, ordering and the time between questions on responses.MethodsA Computer Assisted Telephone Interviewing (CATI) survey was used to re-administer questions collected as part of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Using self-report data, the AIHW estimated that osteoarthritis affects 8.0% of all Australians adults, back pain 7.1%, osteoporosis 3.1%, and rheumatoid arthritis 1.9%. However, the use of self-reported information can undermine the ability to truly identify the scale of MSK within the population, especially for chronic pain, as the reliability of this information is also affected by question wording [ 15 ]. According to the BEACH program, chronic pain among Australian patients attending general practices changed from 18% in 2005 ( N = 3211) to 19% in 2008–09 ( N = 5793) [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using self-report data, the AIHW estimated that osteoarthritis affects 8.0% of all Australians adults, back pain 7.1%, osteoporosis 3.1%, and rheumatoid arthritis 1.9%. However, the use of self-reported information can undermine the ability to truly identify the scale of MSK within the population, especially for chronic pain, as the reliability of this information is also affected by question wording [ 15 ]. According to the BEACH program, chronic pain among Australian patients attending general practices changed from 18% in 2005 ( N = 3211) to 19% in 2008–09 ( N = 5793) [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few surveys have used self-reported data to investigate the prevalence of these conditions among Australian adults [ 6 , 9 , 10 ], while the Bettering the Evaluation and Care of Health (BEACH) program reported encounter rates and medication use for MSK and chronic pain in adults attending a random sample of Australian general practices [ 11 , 12 ]. Estimates for MSK and chronic pain vary across studies and information bias has been highlighted as one of the reasons for these differences [ 13 15 ]. Self-report for chronic pain and some MSK is less accurate than for sociodemographic characteristics, lifestyle, or other chronic conditions, thus affecting the ability of population-based surveys to provide accurate estimates for the total burden of MSK [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, concern regarding the validity and reliability of using self-report measures to evaluate musculoskeletal complaints has been documented in previous literature. 47,48 We attempted to addressed this issue by using validated assessments, but our reliance on using patient-reported outcomes to determine hip functionality and psychological comorbidity could affect the internal validity of the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lo, et al suggested caution with self-reported arthritis to determine prevalence because these authors demonstrated only moderate agreement between the self-report and the reference standard of musculoskeletal (MSK) signs or symptoms, and a sensitivity of 66.7% and specificity of 75.5% 4 . Other studies have demonstrated good to excellent recall of self-reported, doctor-diagnosed arthritis using population surveys 5,6 .…”
mentioning
confidence: 99%